Aplikasi Pupuk Hayati Mikrobat Untuk Meningkatkan Produktivitas Pertanaman Padi Desa Bulu Allaporenge Kabupaten Bone - Hatta Jamil; Zainal Zainal; Muhammad Yunus; Baharuddin Baharuddin; Mustika Tuwo (Jurnal Ilmu Alam dan Lingkungan, 2020)
Rice is the main commodity for most agricultural communities in Indonesia and is still main food ingredient needed by around 90% of Indonesian population. Rice production in South Sulawesi varies greatly between 3 to 7 tons per hectare of dry un-husked rice in normal season conditions. Condition of food crops in Bone District is supported by paddy fields in several districts. Bone District is area with the largest rice production in South Sulawesi. The use of biological fertilizers needs to be developed in an effort to reduce the use of synthetic chemicals. Application of biological fertilizer becomes an excellent complement, because in addition to increasing soil fertility it also spurs plant growth. Application of Mikrobat biofertilizers is carried out on rice plantations located in Bulu Allaporenge Village, Bengo Sub-District, Bone District. Process of giving Mikrobat fertilizer is carried out 15-20 DAPs (days after planting). Treatment of Mikrobat biofertilizers at a dose of 1 liter per hectare at a ratio of 1: 100. The results of application of Mikrobat biofertilizer technology have a significant effect on plant height, panicle length, number of grain per panicle and weight of 1000 grains. While variable number of tillers and percentage of empty grains had no significant effect. The response of farmers is very high to apply biofertilizer technology on rice plantations because farmers immediately see the appearance of good plant growth compared to controls (without the application of microbial fertilizer).